2022
DOI: 10.3390/cells11071106
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of Doxorubicin-Mediated Stress-Induced Premature Senescence in Human Chondrocytes

Abstract: Accumulation of senescent chondrocytes is thought to drive inflammatory processes and subsequent cartilage degeneration in age-related as well as posttraumatic osteoarthritis (OA). However, the underlying mechanisms of senescence and consequences on cartilage homeostasis are not completely understood so far. Therefore, suitable in vitro models are needed to study chondrocyte senescence. In this study, we established and evaluated a doxorubicin (Doxo)-based model of stress-induced premature senescence (SIPS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Similar to our study, Dezfouli et al described lengthening of the G2 phase 14 days after Dox treatment of different aged mouse MSCs [ 47 ]. In contrast, others have found that Dox treatment arrested cell proliferation in G1 phase in human ASCs and chondrocytes [ 32 , 45 ]. To the fact that senescent hallmarks are neither exclusively nor universally expressed in senescent cells, we performed a multi-level characterization to confirm the senescent state of our models.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to our study, Dezfouli et al described lengthening of the G2 phase 14 days after Dox treatment of different aged mouse MSCs [ 47 ]. In contrast, others have found that Dox treatment arrested cell proliferation in G1 phase in human ASCs and chondrocytes [ 32 , 45 ]. To the fact that senescent hallmarks are neither exclusively nor universally expressed in senescent cells, we performed a multi-level characterization to confirm the senescent state of our models.…”
Section: Discussionmentioning
confidence: 94%
“…Stress-induced premature senescence (SIPS) is commonly triggered by exposure to sub-lethal stress in terms of oxidative stress [ 28 ], irradiation [ 29 ] or DNA damaging agents. The cytostatic drug and chemotherapeutic agent Doxorubicin (Dox) induces either apoptosis or senescence in a dose- and time-dependent manner [ 30 , 31 ] and is frequently applied for induction of SIPS [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…SASPs can be produced not only by chondrocytes, but also by other cells within the OA joint, such as osteoblasts, synovial fibroblasts, and macrophages [ 44 ]. For example, TGF-β and IL-6 are both SASP factors that can contribute to chondrocyte aging by activating p15, p21, and p27, therefore, promoting its senescence through the SMAD complex or STAT3 pathway [ 45 , 46 ]. Additionally, the release of SASPs by senescent chondrocytes can produce a chemotactic effect on surrounding immune cells; thus, establishing an inflammatory environment further stimulates cartilage degradation [ 43 ].…”
Section: Pathogenesis Of Oamentioning
confidence: 99%
“…5 Accumulating evidence suggests that an imbalance in the redox state, leading to oxidative stress in chondrocytes, is a key event that perturbs cartilage homeostasis during OA development. 6,7 Oxidative stress activates proinflammatory pathways 8 and can trigger an inflammatory response 9 and chondrocyte senescence, 10 thereby accelerating the degradation of cartilage ECM during OA pathogenesis. 11 Previous clinical studies have illustrated that oxidative stress, aging, and OA are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the progress of OA is associated with biological factors that disrupted the well‐being of chondrocytes and lead to an abnormal state 5 . Accumulating evidence suggests that an imbalance in the redox state, leading to oxidative stress in chondrocytes, is a key event that perturbs cartilage homeostasis during OA development 6,7 …”
Section: Introductionmentioning
confidence: 99%